A Patient with Multiple Gastrointestinal Carcinoid Tumours Presenting with Jejunal Intussusception - Kavinda Deshapriya Bandara; Sanjeevan Ravindrakumar; Kirushanthan Veerasingam; Umesh Jayarajah; V. S. D. Rodrigo (Case Reports in Surgery)
Carcinoid tumours are neuroendocrine tumours which arise from the enterochromaffin cells in the gastrointestinal and bronchopulmonary systems. The presentation of multiple gastrointestinal carcinoids with jejunal intussusception is rare, and the diagnosis may be challenging. A 49-year-old patient with adult onset bronchial asthma presented with pain around the umbilical region for 1-day duration. Physical examination revealed only mild abdominal tenderness. Abdominal computed tomography revealed small bowel intussusception with two separate highly vascular tumours arising in the small bowel mesentery. Exploratory laparotomy was done, with resection of the tumours arising from the small bowel mesentery and the proximal jejunum causing the intussusception which were excised. Histopathological diagnosis confirmed the presence of a Grade 1 carcinoid tumour of classic type. After surgery, he had an uneventful recovery and was asymptomatic. Carcinoid tumours are a very rare cause of adult intussusception. So far, there have been only two reported cases of jejunal intussusception secondary to carcinoid tumours. These will require a combination of surgical intervention and systemic therapy in selective cases for complete management.